Дослідження електрофізичних та агрогідрологічних властивостей ґрунтів - Чушкіна, І. В.; Максимова, Н. М.; Орлінська, О. В.; Коваленко, В. В.; Chushkina, I. V.; Maksymova, N. M.; Orlinska, O. V.; Kovalenko, V. V. (Херсонський державний аграрно-економічний університет, 2021)
Мета роботи - дослідження залежності між агрогідрологічними та електрофізичними властивостями ґрунтів та оцінювання можливості їх застосування в якості піґрунтя експрес-діагностики сільськогосподарських угідь.

Investigate the mineral composition of coal sludge and determine its effect on the properties, structural bonds and structure of dispersed systems from them. The research technique consists in the application of methods for measuring the structural and mechanical properties of dispersed systems. To assess the characteristics of the mechanical properties of structured dispersed systems, the most rational methods are to determine their deformation properties: strength - ultimate shear stress, modulus of elasticity and relaxation characteristics. Macroscopic and optical methods were used to study the mineral composition of sludges from coal concentrators.
Investigation of electrophysical and agrohydrological properties of soilsGoal
Keywords: електричний опір; вертикальне електричне зондування; вологість; температура; ґрунти; засоленість ґрунтів; dispersed systems; structural connections; waste; coal industry; processing; technological solutions; physical and mechanical properties; mineral composition